2020
DOI: 10.1097/brs.0000000000003340
|View full text |Cite
|
Sign up to set email alerts
|

Can the American College of Surgeons Risk Calculator Predict 30-day Complications After Spine Surgery?

Abstract: Mini It is unclear whether the ACS NSQIP Surgical Risk Calculator can predict 30-day complications after lumbar and cervical spinal fusions. This study shows that the Risk Calculator is only of marginal benefit in predicting outcomes in cervical fusion and unlikely to be of benefit in lumbar fusions. Study Design. Retrospective cohort study. Objective. The aim of this study was to assess the American College… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…This risk calculator has been demonstrated to be an effective tool in other orthopedic subspecialties, including joint arthroplasty and spine. 17,26 Patients with diabetes and Charcot foot arthropathy represent a unique population of patients with multiple medical comorbidities. 19,20,22 Their quality of life is severely negatively impacted by the acquired deformity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This risk calculator has been demonstrated to be an effective tool in other orthopedic subspecialties, including joint arthroplasty and spine. 17,26 Patients with diabetes and Charcot foot arthropathy represent a unique population of patients with multiple medical comorbidities. 19,20,22 Their quality of life is severely negatively impacted by the acquired deformity.…”
Section: Introductionmentioning
confidence: 99%
“…This risk calculator has been demonstrated to be an effective tool in other orthopedic subspecialties, including joint arthroplasty and spine. 17,26…”
Section: Introductionmentioning
confidence: 99%
“…The ACS NSQIP have implemented regular auditing procedures that have yielded data with excellent reliability that has continued to improve over time [11]. Additionally, the database has been utilized extensively to identify the incidence of and risk factors for a variety of short-term complications following a variety of orthopaedic procedures [12][13][14].…”
Section: Data Sourcementioning
confidence: 99%
“…A notable tool used for all types of surgeries is the American College of Surgeon’s National Surgical Quality Improvement Program’s (ACS NSQIP) online calculator, which utilizes 21 inputted preoperative factors to predict both LOS and discharge status 17. While met with moderate accuracy for general surgical procedures, numerous studies have shown that it does not provide accurate predictions for patients undergoing spine surgery 18–21…”
mentioning
confidence: 99%